Pulmonary Vein Isolation With Very High Power, Short Duration, Temperature-Controlled Lesions: The QDOT-FAST Trial - Reddy, Vivek Y; Grimaldi, Massimo; De Potter, Tom; Vijgen, Johan M; Bulava, Alan; Duytschaever, Mattias; Martinek, Martin; Natale, Andrea; Knecht, Sebastien; Neuzil, Petr; Pürerfellner, Helmut (JACC. Clinical electrophysiology, 2019)
OBJECTIVES: This study sought to evaluate the safety and short-term performance of a novel catheter for very high power-short duration (vHPSD) ablation in the treatment of paroxysmal atrial fibrillation. BACKGROUND: The vHPSD catheter is a novel contact force-sensing catheter optimized for temperature-controlled radiofrequency ablation with microelectrodes and 6 thermocouples for real-time temperature monitoring; the associated vHPSD algorithm modulates power to maintain target temperature during 90 W, 4 s lesions. METHODS: QDOT-FAST (Clinical Study for Safety and Acute Performance Evaluation of the THERMOCOOL SMARTTOUCH SF-5D System Used With Fast Ablation Mode in Treatment of Patients With Paroxysmal Atrial Fibrillation) is a prospective, multicenter, single-arm study enrolling patients with symptomatic paroxysmal atrial fibrillation indicated for catheter-based pulmonary vein isolation. Primary endpoints were short-term effectiveness (confirmation of entrance block in all targeted pulmonary veins after adenosine/isoproterenol challenge) and short-term safety (primary adverse events). Participants were screened for silent cerebral lesions by magnetic resonance imaging. Patients were followed for 3 months post-ablation. RESULTS: A total of 52 patients underwent ablation and completed follow-up. Pulmonary vein isolation was achieved in all patients using the study catheter alone, with total procedure and fluoroscopy times of 105.2 ± 24.7 min and 6.6 ± 8.2 min, respectively. Most patients (n = 49; 94.2%) were in sinus rhythm at 3 months. Two primary adverse events were reported: 1 pseudoaneurysm; and 1 asymptomatic thromboembolism. There were no deaths, stroke, atrioesophageal fistula, pulmonary vein stenosis, or unanticipated adverse device effects. Six patients had identified silent cerebral lesions-all classified as asymptomatic without clinical or neurologic deficits. CONCLUSIONS: This first-in-human study of a novel catheter with optimized temperature control demonstrated the clinical feasibility and safety of vHPSD ablation. Procedure and fluoroscopy times were substantially lower than historical standard ablation with point-by-point catheters. (Clinical Study for Safety and Acute Performance Evaluation of the THERMOCOOL SMARTTOUCH SF-5D System Used With Fast Ablation Mode in Treatment of Patients With Paroxysmal Atrial Fibrillation [QDOT-FAST]; NCT03459196).
Keywords: Microelectrodes; prospektivní studie; léčebná irigace; Humans; lidé; Pulmonary Veins; venae pulmonales; fibrilace síní; Equipment Design; lidé středního věku; Treatment Outcome; Atrial Fibrillation; Middle Aged; design vybavení; Fluoroscopy; Female; mikroelektrody; Male; Prospective Studies; výsledek terapie; mužské pohlaví; Aged; Catheter Ablation; katetrizační ablace; fluoroskopie; Therapeutic Irrigation; ženské pohlaví; Catheters; katétry; senioři